1989
DOI: 10.1002/aic.690350806
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of theories for gas absorption with chemical reaction

Abstract: Steady-and unsteady-state theories for interfacial mass transfer are used to model gas absorption with second-order, reversible reaction and the absorption of CO, into aqueous MDEA (methyldiethanolamine). The latter case represents a system of industrial interest, having both finite rate and equilibrium reactions. Steady-state theories studied are film theory, simplified eddy diffusivity theory, and an approximation to surface renewal theory. Higbie's penetration and Danckwert's surface renewal theories are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 30 publications
1
58
0
Order By: Relevance
“…All relevant reactions, which take place if CO, is absorbed in an aqueous solution of a tertiary amine, were incorporated in the flux model (reactions 1, 2, 8 and 10). Model equations and initial and boundary conditions were similar to those applied by Glasscock and Rochelle ( 1989). Numerical techniques used were identical to those applied by Versteeg et al (1989).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All relevant reactions, which take place if CO, is absorbed in an aqueous solution of a tertiary amine, were incorporated in the flux model (reactions 1, 2, 8 and 10). Model equations and initial and boundary conditions were similar to those applied by Glasscock and Rochelle ( 1989). Numerical techniques used were identical to those applied by Versteeg et al (1989).…”
Section: Methodsmentioning
confidence: 99%
“…Among others, Pohorecki and Moniuk (1988) presented a correlation for k,,-. Glasscock and Rochelle (1989), however, showed that significant depletion of OH-at the interface may occur. In their excellent model, they took into account four reactions: the finite rate reactions, C0,-amine and C0,-OH-, and the instantaneous equilibria reactions, amine-H,O and carbonate-bicarbonate (reactions 1, 2,8 and 10).…”
Section: Oh-contributionmentioning
confidence: 97%
“…For unequal diffusivities Glasscock and Rochelle (1989) showed that large differences for the asymptotic enhancement factor occur between the film model and surface renewal or penetration theory, respectively. Chang and Rochelle (1982) showed that by using the square root of the diffusivity ratio in the film model, the film-and surface-renewal model give almost the same enhancement factors in the instantaneous absorption regime for the reaction A+B~C.…”
Section: Adaptation Of the Asymptotic Enhancement Factor Of Secor Andmentioning
confidence: 99%
“…As mentioned before, the results of the incorporation of the influence of the reaction on the mass transfer rate are usually presented in terms of the enhancement factor. Glasscock and Rochelle (1989) showed that, for the models mentioned, considerable differences for the numerically calculated enhancement factors could occur at identical process conditions. The differences between the penetration and surface renewal model were generally small, while the film model showed larger deviations.…”
mentioning
confidence: 99%
“…Glasscock and Rochelle implemented the Nernst-Planck equation to take this electric potential into account [33]. They calculated the electric potential using the Henderson equation.…”
Section: Introductionmentioning
confidence: 99%